Effect of promotion pressure and financial burden on investment in public–private partnership infrastructure projects in China. (21st October 2019) - Wang, Ling; Zhou, Lihong; Xiong, Yan; Yan, Dongyi
Abstract : By identifying the political motives of officials and local governments, this study aims to provide a new political economic analysis framework for understanding China's incentives for investing in public–private partnership (PPP) infrastructure projects. Chinese urban panel data for the period 2013–17 were used to examine the mechanisms of promotion pressure and financial burden in relation to investments in PPP infrastructure projects. Based on our findings, the following policy recommendations are proposed: standardise the behaviour of local government officials in promoting PPP projects, establish a lifelong accountability mechanism for PPP project performance, establish a mechanism for local government debt risk assessment and prevention, and avoid the risk of local debt arising from over‐investment in PPP infrastructure projects. Moreover, a match should be formed between local economic infrastructure planning and investment plans to avoid over‐ or under‐investment.